Regional differences in movement behaviours of children and youth during the second wave of the COVID-19 pandemic in Canada: follow-up from a national study - Caldwell, Hilary A.T.; Faulkner, Guy; Tremblay, Mark S.; Rhodes, Ryan E.; de Lannoy, Louise; Kirk, Sara F.L.; Rehman, Laurene; Moore, Sarah A. (Canadian journal of public health, 2022)
Objectives Public health restrictions varied by region during the COVID-19 pandemic and reduced opportunities for children to be physically active. The purpose of this study was to assess regional differences in movement behaviours of Canadian children and youth during the second wave of the COVID-19 pandemic. Methods A national sample of Canadian parents ( n =1568; 58% women) of children and youth (5–17 years of age) completed an online survey. Participants were classified based on region of residence (British Columbia, Prairies, Ontario, Quebec, or Atlantic Canada). Differences in movement and play behaviours (physical activity, outdoor play, sleep, screen time) between children and youth living in different regions were examined. Results Compared to children and youth in Quebec (the region with the highest COVID-19 prevalence), children and youth in the Prairies ( F (1,1563) =9.0, p =0.01) and Atlantic Canada ( F (1,1563) =17.1, p <0.001) participated in more moderate-to-vigorous physical activity (MVPA). Compared to Quebec, living in Atlantic Canada increased the odds of meeting the MVPA guideline (odds ratio (OR)=2.1, p =0.02), living in Ontario decreased the odds of meeting the sleep guideline (OR=0.6, p =0.01), and living in Ontario (OR=0.7, p =0.04) or Atlantic Canada (OR=0.6, p =0.049) decreased the odds of meeting the screen time guideline. Children and youth in Atlantic Canada demonstrated smaller declines in outdoor play than their counterparts in Quebec. Conclusion Movement and play behaviours varied between regions of Canada where the highest COVID-19 prevalence corresponded to lower odds of meeting the physical activity guidelines. Low compliance with 24-hour movement guidelines suggests that regional pandemic recovery plans need to prioritize opportunities for healthy movement.